Performance, behaviour and organization of maize trading in Malawi - Henry Kankwamba; Lukas Kornher (Agricultural and Food Economics, 2019)
Industry structure and social capital could affect traders, market performance and distribution of economic resources such as food. This study assesses the effect of industry structure and social capital on traders' profitability and resilience. We use Bayes Model Averaging regression techniques to draw inferences from a random, representative and systematically selected sample of maize traders in the central region of Malawi. We complement our results with key informant prior information from industry experts and literature. Results indicate that at the local market level, few traders dominate but competition increases when we consider the entire district and region. Results also show that interaction with distant traders and brokers is associated with more profitable and resilient businesses. While we find evidence that social capital is positively associated with business profitability, results do not strongly support the hypothesis that other measures of social capital such as tribal and religious affiliation have an effect on traders' resilience. Noteworthy, as the unit of closeness among traders decreases to family ties, profits tend to increase. This suggests a more group and kin selective evolutionary stable strategy among maize traders.
Keywords: 330; Profitability; Social capital; Resilience; Bayesian regression; Herfindahl Index; Maize traders; Kin selection